Health education for elderly with hypertension in RW 17 Mojosongo Jebres Surakarta - Shahad Erma Nurhayati; Alinda Nur Ramadhani; Nabela Umi Karomah; Muslimaini Muslimaini; Rizki Wahyudi; Sisca Setyaningrum; Siti Anisa; Sonia Ananda Firdaus (Universitas Muhammadiyah Magelang, 2023)
Hypertension in the elderly has a high prevalence, which is due to the decline in organ function in the elderly. Based on the previous research, it was found that blood pressure was originally high, but after being given the intervention of slow deep breathing, stretching, and brisk walking exercise, it obtained relevant depreciation. With this counseling, it is hoped that all people, especially the elderly who have a history of high blood pressure, can increase their knowledge about exercises that can be done to reduce high blood pressure. This program included counseling about hypertension and exercises that could be done by the elderly to reduce high blood pressure. The evaluation result shows that there is an increase in the knowledge of the elderly about a healthy lifestyle by 8% for a good level of knowledge.